Hydraulic Analysis and Water CAD simulation of the Water Distribution Network applied to marine Recirculating Aquaculture Systems - Anibal Verástegui-Maita; Jesús Mejía; Néstor Montalvo; Absalón Vasquez (Kurdish Studies, 2024)
Water supply is crucial for all human activities, especially when large volumes and high quality are required. Therefore, greater efficiency is sought in water storage, distribution, use and reuse systems. The present design and simulation work was carried out simultaneously with the physical installation of a Recirculating Aquaculture System (RAS) for the breeding of the marine fish Chita in Callao - Peru. The sizing of the RAS components and hydraulic characterization was carried out by applying mass balance theory, using an Excel spreadsheet and hydraulic simulation of the distribution network with WaterCAD software. The objective was to apply these software tools and compare the simulation results with parameters conventionally used in the design of RAS installations, and to investigate head losses, hydraulic pressure and diameter assignment in the pipe network. Demonstrating the adaptability of WaterCAD in the verification of pressures, flow rates and flow velocities in the distribution of water in a RAS, and finding that the diameters conventionally used, based solely on empirical criteria, were 7.76% larger than those of the simulation. Consequently, it is deduced that the hydraulic parameters present significant differences that must be considered to conceptualize an adequate water distribution network. The introduction of WaterCAD simulation in the design and operation of the RAS system is recommended to obtain safer pipe networks, that guarantee the stable state condition of the RAS system. Opening the possibility of more stable water flows, with lower energy costs associated to the operation of pumps.